Changes in physical and chemical properties of Hemic and Sapric peat influenced by liming and fertilizer application - Abdul Reeza, Ameera (2015)
Studies on peat of tropical regions on their physical and chemical changes as a consequence of liming and fertilizers are mostly inconclusive due to the variations in the type of peat, climate, hydrology as well as the botanical origin of the peat lands. Hence, this study was conducted to determine the changes in physical and chemical properties specifically in Hemic and Sapric peat material upon liming and fertilizer application; to compare the rate of carbon dioxide release between Hemic and Sapric peat material upon lime and fertilizer application under a small-scale laboratory incubation study; to evaluate the effect of liming and fertilizer on availability of Nitrogen (N), Phosphorus (P), Potassium (K) in Hemic and Sapric material; to examine the changes in the level of Carbon (C) and N content in the two types of peat materials as a result of lime and fertilizer application during the course of planting maize and the availability of N for the plant. Experiments were conducted both in laboratory and netted-house where the first and final objectives were conducted using the same experiment where maize were grown until tasselling stage (8 weeks) in the netted-house of Ladang 16, UPM. Four treatments in triplicates were applied (C) control; (T1) compound fertilizer NPK (12:12:17:2); (T2) dolomite adjusted to pH5.5; (T3) combination of compound fertilizer NPK and dolomite adjusted to pH5.5. The second objective was conducted using an open chamber incubation approach to capture CO2 release while the third objective was assessed by using basins of 32 x 15 cm dimension with temperature setting of 30°C. Three treatments applied in the latter two studies in triplicates were (T1) no additives; (T2) addition of lime at 2.5 g per 100 g of peat; (T3) addition of lime and fertilizer NPK (12:12:17:2) at 3 g per 100 g of peat. The peat materials were left to decompose aerobically for 8 weeks and samples were taken for the determination of CO2 –C, available N, P and K at every 7 days interval.The addition of lime (T2) and fertilizers (T3) caused significant increases in pH from pH 3.7-3.8 to pH 5.6-5.79 and CEC from an average of 121.1 meq 100g-1 to 233.9 meq 100g-1 while significantly reducing the organic carbon (average of 53.6% to 50.0%), MWD (average of 4.4 mm to 3.1 mm) and water availability (average of 78.7% to 34.1%) of the two types of peat material. The use of FTIR further justify the enhanced decomposition in the T2 and T3 by the disappearance of aliphatic and aromatic C=C stretch at 1700 and 1600 cm-1. Sapric material often showed higher carbon dioxide release than Hemic regardless of treatment application. The response patterns on nutrient availability were similar between the two peat materials, only that they differ between treatments. Although NH4+ was significantly lower in T2 (202.13 mg kg-1) compared to T1 (264.07 mg kg-1) in Hemic, however the release may persist longer in T2 as the response was linear compared to T1 where response was quadratic. The introduction of lime (T2) did not improve the release of P (58.7-73.2 mg kg-1) compared to under controlled condition (79-96.5 mg kg-1). Liming peat material also resulted in lower amounts of exchangeable K+ (19.27- 27.72 mg kg-1) compared to under controlled condition (21.73-33.89 mg kg-1). Maize plants were unable to grow in the control and T1 due to the extreme acidity of the peat materials as they grew only when the peat materials were amended with lime in T2 and T3. Although no significant differences found on N concentrations in maize plants when planted on the two types of peat material, yet the maize plants showed better growth when planted on Sapric. However, the N content in the plant was significantly reduced in the second planting for T2 (15.25-26.34 mg kg-1) compared to the same treatment during the first planting (65.63-90.88 mg kg-1) due to the decline of ammonium supply in these peat materials. Treatment with both application of lime and fertilizer (T3) showed highest dry matter weight in the two plantings. Although the practice of lime and fertilizer application in Hemic and Sapric material resulted in higher nutrient availability (N, P and K), however, this practice also resulted in higher amounts of carbon dioxide release with time, breakdown of larger-sized aggregates of organic material as well as reduction in water retention capability which in turn may induce the susceptibility of wind and water erosion of this fragile peat materials.